Macrophages CD163+ and Factor XIIIa+ Provide a First-Line Defence against Proliferative Verrucous Leukoplakia Antigens - Palaçon, Mariana Paravani [UNESP] (2023)
This study aimed to evaluate the density of the dendritic cells (DCs) and macrophages in oral leukoplakia (OL) and proliferative verrucous leukoplakia (PVL) by immunohistochemical analysis. We analysed paraffined tissue samples of PVL (n = 27), OL (n = 20), and inflammatory fibrous hyperplasia (n = 20) as the control group using the immunomarkers for DCs (CD1a, CD207, CD83, CD208 and CD123) and macrophages (CD68, CD163, FXIIIa and CD209). A quantitative analysis of positive cells in the epithelial and subepithelial areas was determined. Our results showed a reduction in CD208+ cells in the subepithelial area of the OL and PVL compared to the control. Additionally, we found a higher density of FXIIIa+ and CD163+ cells in the subepithelial area in PVL compared to the OL and control. Four-way MANOVA revealed a relationship between increased CD123+ cell density in the subepithelial area of “high-risk” samples regardless of disease. Macrophages provide the first line of defence against PVL antigens, suggesting a distinct pattern of innate immune system activation in PVL compared to OL, which may contribute to the complexity and the high rate of malignant transformation in the PVL.